2014
DOI: 10.1186/1742-4755-11-58
|View full text |Cite
|
Sign up to set email alerts
|

The experience of dysmenorrhoea among Ghanaian senior high and university students: pain characteristics and effects

Abstract: BackgroundDysmenorrhoea is a common problem of women at the reproductive age and may have negative effect on the education of females at various stages on the educational ladder.Context and purposeThis study sought to gain an in-depth understanding of the experience of dysmenorrhoea and its effect on female students in a secondary and a tertiary institution in Accra, Ghana.MethodsThe study employed a descriptive phenomenology design and was conducted at a University and a Senior High School (SHS) in Accra. Pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 23 publications
4
38
0
17
Order By: Relevance
“…The prevalence of dysmenorrhoea in Asia ranges from 58.8% to 84.9% (Chan, ; Mahkam, Joffres, Corber, Bayanzadeh, & Mahnaz, ). Various studies in Africa have reported that the prevalence ranging from 58% to 85.4% (Aziato, Dedey, & Clegg‐Lamptey, ; Nooh, ). However, there is paucity of evidence available about the prevalence of dysmenorrhoea in East Africa where Uganda is located.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of dysmenorrhoea in Asia ranges from 58.8% to 84.9% (Chan, ; Mahkam, Joffres, Corber, Bayanzadeh, & Mahnaz, ). Various studies in Africa have reported that the prevalence ranging from 58% to 85.4% (Aziato, Dedey, & Clegg‐Lamptey, ; Nooh, ). However, there is paucity of evidence available about the prevalence of dysmenorrhoea in East Africa where Uganda is located.…”
Section: Introductionmentioning
confidence: 99%
“…prevalence ranging from 58% to 85.4% (Aziato, Dedey, & Clegg-Lamptey, 2014;Nooh, 2014). However, there is paucity of evidence available about the prevalence of dysmenorrhoea in East Africa where Uganda is located.…”
mentioning
confidence: 99%
“…El dolor que produce la dismenorrea perturba la calidad de vida de las mujeres que la padecen (Iacovides et al, 2014). Según diferentes estudios, la intensidad media del dolor es de aproximadamente 6 puntos en Escala Visual Analógica (EVA) (Aziato et al, 2014;Iacovides et al, 2014;Wong, 2018). Además, se asocian otros signos y síntomas como cefalea (Aziato et al, 2014;Knox et al, 2015;Rani et al, 2016;Rupa Vani, Veena, Subitha, Hemanth Kumar, & Bupathy, 2013;Carman et al, 2018)), cansancio (Omidvar, Bakouei, Amiri, & Begum, 2016), síntomas digestivos (Aziato et al, 2014;Al-Jefout et al, 2015;Knox et al, 2015;Rani et al, 2016;Rupa Vani et al, 2013;Aktaş, 2015) dolor musculoesquelético (Aziato et al, 2014;Al-Jefout et al, 2015;Omidvar et al, 2016;Aktaş, 2015), hinchazón abdominal y de extremidades (Rupa Vani et al, 2013;Kwame, Amalba, & Mohammed, 2018).…”
Section: Consecuencias De La Dismenorrea Primaria Sobre La Salud Físiunclassified
“…La dismenorrea primaria se define como calambres dolorosos de tipo espasmódico en el abdomen inferior, en ausencia de patología orgánica pélvica (Iacovides, Avidon, & Baker, 2015;Ju, Jones, & Mishra, 2014;Tanmahasamut & Chawengsettakul, 2012). El dolor puede describirse como "corte", "puñalada", "calambre" y/o "ardor" (Aziato, Dedey, & Clegg-Lamptey, 2014). Generalmente, aparece con el inicio de la menstruación o pocas horas después y puede llegar a prolongarse desde ocho hasta 72 horas (Iacovides et al, 2015;Mavrelos & Saridogan, 2017;Harel, 2008).…”
Section: Introductionunclassified
“…É caracterizada por se apresentar na ausência de patologia pélvica, podendo vir acompanhada de outros sinais e sintomas característicos como cefaleia 2,3,4 , diarreia 2,4 , irritação 3,4 , perda de apetite 2 , lombalgia 2,3 , náusease vômitos impactando no rendimento das atividades de vida diária 2,3,4 . A etiologia é atribuída principalmente à liberação e atuação das prostaglandinas no tecido uterino, provocando contrações espasmódicas dolorosas, com isquemia e hipersensibilização dos nervos periféricos locais 4,5 .…”
unclassified